11 - Creating Sustainable Learning Environments for Professional Curriculum Leadership through Information and Communication Technologies - Mahlomaholo, Sechaba; Tshelane, Molaodi (Journal of Higher Education in Africa, 2022)
This paper documents the processes and procedures followed by a team of two researchers and five co-researchers in the creation of sustainable learning environments at a school in the Free State province of South Af- rica. For this purpose, we used one school to illustrate how diverse school community members deliberately constructed a framework for the integra- tion of ICT in the development of its professional curriculum leadership practices. A conceptual framework driven through critical emancipatory theory is applied as the lens that propels us to create opportunities for self-empowerment. Grounded on this theoretical framing we then used a participatory action research to operationalize it. We generated relevant data through the establishment of a research team, which coalesced around a common vision collectively identified in pursuance of the aim of study. Data generated were analysed using Van Dijk’s critical discourse analysis. The findings discussed are (i) performance through reflecting on professional curriculum practices, (ii) their actions, (iii) procedures involved therein, and (iv) strategies. The contribution we made was a tested framework for the integration of ICT in a professional curriculum context. This contribution has implications for the creation of a sustainable learning environment.